2022
DOI: 10.1002/ejsp.2884
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of income inequality on health: The role of perceived competitiveness and avoidance/approach motivation

Abstract: Income inequality is commonly posited to elevate concerns about social status that undermine psychological health, but the empirical evidence is inconsistent. Here we propose that these inconsistencies conceal opposing processes: Income inequality prompts perceived competitiveness, which can both negatively predict psychological health via avoidance motivation and positively predict psychological health via approach motivation. First, we conducted a two-year longitudinal study (1,700+ participants from 500+ co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 114 publications
0
13
0
Order By: Relevance
“…Past experimental work supports the causal link between perceptions of competition and these motivational goals (e.g., Pekrun et al, 2014; Shin et al, 2017), and the present findings suggest that perceptions of interracial competition can elicit approach- and avoidance-oriented responses. However, the link between racial income inequality, perceived interracial competition, and approach-avoidance motivation have yet to be examined (although has been investigated on the subject of general income inequality and competition broadly; see Sommet & Elliot, 2023). As such, future research may benefit strongly from expanding the present work by integrating race-based income inequality, intergroup competition, and motivational processes together in a comprehensive model.…”
Section: Discussionmentioning
confidence: 99%
“…Past experimental work supports the causal link between perceptions of competition and these motivational goals (e.g., Pekrun et al, 2014; Shin et al, 2017), and the present findings suggest that perceptions of interracial competition can elicit approach- and avoidance-oriented responses. However, the link between racial income inequality, perceived interracial competition, and approach-avoidance motivation have yet to be examined (although has been investigated on the subject of general income inequality and competition broadly; see Sommet & Elliot, 2023). As such, future research may benefit strongly from expanding the present work by integrating race-based income inequality, intergroup competition, and motivational processes together in a comprehensive model.…”
Section: Discussionmentioning
confidence: 99%
“…Sommet and Elliot (2023) recently proposed that the absence of an overall link between income inequality and well-being concealed opposing motivational processes. In a 2-year longitudinal study, they found that income inequality predicted perceived competitiveness, which itself (a) negatively predicted well-being via avoidance motivation (sample item: “In general, I am focused on preventing negative events in my life”) and (b) positively predicted well-being via approach motivation (sample item: “I typically focus on the success I hope to achieve in the future”).…”
Section: The Psychology Of Income Inequality Through the Lens Of Comp...mentioning
confidence: 99%
“…Individuals exposed to chronic or temporary inequality are more individualistic and competitive (Moreno-Bella et al, 2019;Sánchez-Rodríguez et al, 2019). Under conditions of high economic inequality, social strategies based on dominance and competition become more frequent (Sommet et al, 2019;Sommet & Elliot, 2022b), because the world might be construed as one where the winner takes it all (Ongis & Davidai, 2022). Economic inequality also heightens individuals' concerns about their standing in society and that they receive enough positive recognition from others (Layte & Whelan, 2014;Melita et al, 2021).…”
Section: Current Perspectives On Economic Inequalitymentioning
confidence: 99%